Targeting DKK3 to remodel tumor immune microenvironment and enhance cancer immunotherapy - Kai Shi; Yan Zhao; Hao Ye; Xiaoming Zhu; Zhenghai Chen (BMC Cancer)
Abstract Cancer immunotherapy such as immune checkpoint blockade (ICB) therapy has made important breakthroughs in cancer treatment, however, currently only parts of cancer patients benefit from ICB therapy. The suppressive tumor immune microenvironment (TIME) impedes the treatment response of immunotherapy, indicating the necessity to explore new treatment targets. Here, we reported a new potential immunotherapeutic target, Dickkopf-3 (DKK3), for cancer treatment. DKK3 expression is up-regulated in the tumors from multiple cancer types, and high DKK3 expression is associated with worse survival outcome across different cancers. We observed that DKK3 directly inhibits the activation of CD8+ T cells and the Th1 differentiation of CD4+ T cells ex vivo. Also, by establishing four different mouse cancer models, we found that DKK3 blockade triggers effective anti-tumor effects and improve the survival of tumor-bearing mice in vivo. DKK3 blockade also remodels the suppressive TIME of different cancer types, including the increased infiltration of CD8+ T cells, IFN-γ+CD8+ T cells, Th1 cells, and decreased infiltration of M2 macrophages and MDSCs in the TIME. Moreover, we found that combined blockade of DKK3 and PD-1 induces synergistic tumor-control effect in our mouse cancer model. Therefore, our study reveals the impact of DKK3 in the TIME and cancer progression, which suggests that DKK3 is a novel and promising immunotherapeutic target for enhanced cancer immunotherapy.